Systematics and biology of Cotesia typhae sp. n. (Hymenoptera, Braconidae, Microgastrinae), a potential biological control agent against the noctuid Mediterranean corn borer, Sesamia nonagrioides - Kaiser, Laure (Zookeys, 2017)
Abstract. Many parasitoid species are subjected to strong selective pressures from their host, and their adaptive response may result in the formation of genetically differentiated populations, called host races. When environmental factors and reproduction traits prevent gene flow, host races become distinct species. Such a process has recently been documented within the Cotesia flavipes species complex, all of which are larval parasitoids of moth species whose larvae are stem borers of Poales. A previous study on the African species C. sesamiae, incorporating molecular, ecological and biological data on various samples, showed that a particular population could be considered as a distinct species, because it was specialized at both host (Sesamia nonagrioides) and plant (Typha domingensis) levels, and reproductively isolated from other C. sesamiae. Due to its potential for the biological control of S. nonagrioides, a serious corn pest in Mediterranean countries and even in Iran, we describe here Cotesia typhae Fernandez-Triana sp. n. The new species is characterized on the basis of morphological, molecular, ecological and geographical data, which proved to be useful for future collection and rapid identification of the species within the species complex. Fecundity traits and parasitism success on African and European S. nonagrioides populations, estimated by laboratory studies, are also included.